Initial teacher education 2024: why inclusion matters? - Sonia Blandford (Quality Education for All)
– Teacher recruitment is under pressure across England with the majority of routes into teaching facing challenges in respect to recruitment and retention. Schools are also challenged by issues of attendance, behaviour and exclusion. This paper examines a way forward that addresses inclusion in the context of initial teacher education. Recent research in the southwest of England serves to illustrate the needs of all teachers to deliver inclusive provision in their schools. Teacher education begins with initial teacher training; irrespective of the route inclusion of all pupils should be understood by all trainees, which would have a positive impact on teacher recruitment and retention.